Evaluation of muscle tissue growth in Young Mediterranean Buffaloes slaughtered at different weights - dos Santos, T. A. B. [UNESP]; Jorge, Andre Mendes [UNESP]; Pardo, R. B. [UNESP] (Pagepress Publ, 2007)
This study evaluated muscle, adipose and bone tissue growth in young Mediterranean buffaloes slaughtered with different weights. Twenty eight non-castrated males, approximately 14 months old and 330 kilos, were distributed in four experimental and one control groups. Received the same diet during a non-fixed period and when reached the pre-established weights (450 kg, 480 kg, 510 kg, 540 kg) were fasted for 16 hours and slaughtered. NRC 1996, level 2, ruminal simulation program for non-castrated animals with a daily weight gain of 1.40 kg determined percentage composition of experimental diet (dry matter): coast cross hay (20.6%), corn silage (7.8%), cotton seed (8.2%), humid corn silage (46%) and commercial mineral concentrate (17.4%), representing 13% of crude protein and 2,68% of metabolizable energy (Mcal/kg). Feed was offered ad libitum twice daily. Slaughter of control group occurred after 30 days of an adaptation period. The other ones were weighted each 28 days until reached pre-established weight. Carcasses were chilled for 18 hours under -5 degrees C. Ninth, 10 degrees and 11 degrees ribs of the half left carcass were submitted to HH section and according to the statistical regression analysis (SAS, 1996), allometric coefficient value was negative (b<1) demonstrating the early growth of muscle in relation to empty carcass weight.
Keywords: Muscle tissue; Buffalo